DAMPAKPENGADAANGABAHOLEHBULOG BERDASARKAN INPRES NOMOR 2 TAHUN 2005 TERHADAP TINGKAT PENDAPATAN RUMAH TANGGADI JAWA TENGAH (Pendekatan Structural Path Analysis dan Dampak Sektoral pada Sistem Neraca Sosial Ekonomi Jawa Tengah) - Firmansyah Firmansyah (Universitas Islam Nahdlatul Ulama Jepara, 2005)
AbstractPoverty and income distribution problems are still the main topic on Indonesia's development. Some government strategies and policies are aimed to solve the problems. One of the policies is the national rice policy that regulates distribution of subsidized rice for poor and determining government purchasing price (HPP) for procurement national rice stock. This study analyze how big the effect of H PP policy and government rice procurement to household income.Most of Indonesia region face on poverty and gap of income distribution problems, include Jawa Tengah region. This study analyze household income pattern in Jawa Tengah. Using clusterization of SAM table, this study explain two problems: a) how big of government demand of rice output influence income of lzouselwlds pattern, and b) how the influence transmits from the pole of injection to the pole of destination.As estimation method, multiplier effect and structural path analyzis (SPA) are conducted for this reseach. Results of estimation show that agriculture enterpreneur household receives largest effect of government rice procurement, whereas, agriculture worker household gets smallest effects. Highest level of income growth are earned by non agricultural high income rural household.Based on transimisio11 path. the effect of agricultural sector final demand - that cause ofgovernment rice procureme11t- to agriculture worker household are transmitted through paid agriculture worker. Meanwhile, the effect are transmitted via unpaid agriculture worker to agriculture enterpreneur household, high and low income rural non agricultural household. For urban non agriculture household, the effect are transmitted through a long path. Keyword: Social accounting matrices (SAM), structural path analysis (SPA), incomedistribution, notional rice stock, national rice policy